Development and implementation of a standardized precompetition medical assessment of international elite football players - 2006 FIFA World Cup Germany - Dvorak, J.; Grimm, K.; Schmied, C.; Junge, A. (Clinical Journal of Sport Medicine, 2009)
Objective: To create a model for the precompetition medical assessment (PCMA) of international elite football players aimed at identifying risk factors and to assess the feasibility of standardized requirements for teams from countries with variable medical standards.